Risk factors of laryngeal injuries in extubated critical pediatric patients - HebatAllah Fadel Algebaly; Mona Mohsen; Maggie Louis Naguib; Hafez Bazaraa; Noran Hazem; Miriam Magdy Aziz (SpringerOpen, 2021)
Abstract Background The larynx in children is unique compared to adults. This makes the larynx more prone to trauma during intubation. Under sedation and frequent repositioning of the tube are recorded as risk factors for laryngeal injury. We examined the larynx of 40 critically ill children in the first 24 h after extubation to estimate the frequency and analyze the risk factors for laryngeal trauma using the classification system for acute laryngeal injury (CALI). Results The post-extubation stridor patients had a higher frequency of diagnosis of inborn errors of metabolism, longer duration of ventilation, longer hospital stay, moderate to severe involvement of glottic and subglottic area, frequent intubation attempts, and more than 60 s to intubate Regression analysis of the risk factors of severity of the injury has shown that development of ventilator-associated pneumonia carried the highest risk (OR 32.111 95% CI 5.660 to 182.176), followed by time elapsed till intubation in seconds (OR 11.836, 95% CI 2.889 to 48.490), number of intubation attempts (OR 10.8, CI 2.433 to 47.847), and development of pneumothorax (OR 10.231, 95% CI 1.12 to 93.3). Conclusion The incidence of intubation-related laryngeal trauma in pediatric ICU is high and varies widely from mild, non-symptomatic to moderate, and severe and could be predicted by any of the following: prolonged days of ventilation, pneumothorax, multiple tube changes, or difficult intubation.